2017
DOI: 10.1007/s11356-017-9110-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical hazard safety awareness among healthcare workers in Tanta university hospitals, Egypt

Abstract: Hospital workers are exposed to many occupational hazards that may threaten their health and safety. Physical hazards encountered in hospital working environment include temperature, illumination, noise, electrical injuries, and radiation. To assess the awareness of healthcare workers (HCWs) about physical hazards in Tanta university hospitals, this cross-sectional study included 401 HCWs (physicians, nurses, technicians, and workers) from seven departments (general surgery, orthopedics, radiology, ophthalmolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Healthcare facilities are environments built for managing people with health challenges but can sometimes create hazards if not well managed. El—Salamy et al (2018) affirmed that hospital environment can sometimes generate irritating sounds with an adverse effect on healthcare staffers and more than one-half of the respondents had poor understanding concerning fire hazards in an hospital environment. This collaborated with Jalali et al (2016) where the healthcare staffers understanding concerning fires and its prevention has been lower than the average limit.…”
Section: Fire Safety Management and Measures In Healthcare Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthcare facilities are environments built for managing people with health challenges but can sometimes create hazards if not well managed. El—Salamy et al (2018) affirmed that hospital environment can sometimes generate irritating sounds with an adverse effect on healthcare staffers and more than one-half of the respondents had poor understanding concerning fire hazards in an hospital environment. This collaborated with Jalali et al (2016) where the healthcare staffers understanding concerning fires and its prevention has been lower than the average limit.…”
Section: Fire Safety Management and Measures In Healthcare Facilitiesmentioning
confidence: 99%
“…This collaborated with Jalali et al (2016) where the healthcare staffers understanding concerning fires and its prevention has been lower than the average limit. El—Salamy et al (2018) recommended that hospital management should always inform staffers concerning the hazards associated with hospital environment and encourage workers via the provision of adequate personal protective equipment. In Nigeria, Manuel et al .…”
Section: Fire Safety Management and Measures In Healthcare Facilitiesmentioning
confidence: 99%
“…Myths or fears can cause wrong practices/avoidance of certain work practices; on the other hand, overconfidence due to ignorance may lead to unnecessary injury or exposure to hazards. It has also been seen in the past that HCWs are aware of their lack of knowledge and information about occupational hazards and realize the need for training and awareness ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…These hazards are very common at work place. There are many reasons for the occurrence of the hazards like most of the nurses and technicians reported that some time protective devices are not available in the department, some time worker not aware how to deal with protective devices in emergency situation [9]. As a leader provide electrical devices for patient shifting.…”
Section: Discussionmentioning
confidence: 99%